2010
DOI: 10.1095/biolreprod.109.080929
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B, Cathepsin L, and Cystatin C in the Porcine Uterus and Placenta: Potential Roles in Endometrial/Placental Remodeling and in Fluid-Phase Transport of Proteins Secreted by Uterine Epithelia Across Placental Areolae1

Abstract: Cathepsins (CTSB and CTSL1) and their inhibitor, cystatin C (CST3), remodel uterine endometrium and placenta for transport of gases, micronutrients, and macromolecules essential for development and growth of the conceptus (embryo/fetus and placental membranes). We examined the temporal/spatial control of expression for CTSB, CTSL1, and CST3 mRNAs in endometria and placentae of pigs using three developmental models: 1) pigs were hysterectomized during the estrous cycle or pregnancy; 2) cyclic pigs were injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 51 publications
1
57
0
Order By: Relevance
“…Although there were more total GE cells in uteri of progesterone-treated gilts than CO-treated gilts, due to increased uterine horn length and endometrial thickness, GE branching and coiling as they extended into the uterine wall were insufficient to maintain GE density. Indeed, GE number and size did not approach levels normally observed on day 40 of pregnancy (Garlow et al 2002, Song et al 2009, 2010. This is in contrast to the vasculature of the uterus, which increased in proportion to the thickness of the uterine wall in shallow regions of the endometrium, and significantly increased in density in the deep endometrium of progesterone-treated pigs compared with CO-treated pigs.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Although there were more total GE cells in uteri of progesterone-treated gilts than CO-treated gilts, due to increased uterine horn length and endometrial thickness, GE branching and coiling as they extended into the uterine wall were insufficient to maintain GE density. Indeed, GE number and size did not approach levels normally observed on day 40 of pregnancy (Garlow et al 2002, Song et al 2009, 2010. This is in contrast to the vasculature of the uterus, which increased in proportion to the thickness of the uterine wall in shallow regions of the endometrium, and significantly increased in density in the deep endometrium of progesterone-treated pigs compared with CO-treated pigs.…”
Section: Discussionmentioning
confidence: 71%
“…2). These LE cells exhibited secretory function because immunoreactive cathepsin B (CTSB), a protease expressed and secreted from the LE of pregnant pigs (Song et al 2010), was detected in the uterine flushings of progesterone-treated pigs (Fig. 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Slides were counterstained with Prolong Gold Antifade reagent with DAPI (Life Technologies, Grand Island, NY; 1:500) and coverslips were added. For in vivo studies, samples were used from a previously conducted study (Song et al, 2010). Sexually mature gilts of similar age, weight and genetic background (F1 crosses of Yorkshire X Landrace sows and Duroc X Hampshire boars) were observed daily for estrus (day 0) and exhibited at least two estrus cycles of normal duration (18 to 21 days) before being used in these studies.…”
Section: Immunofluorescencementioning
confidence: 99%
“…Vallet et al [3] recently concluded that an increased placental function is one of the important contributors to higher prenatal survival in pigs. A primary function of the placenta is the transfer of oxygen, nutrients, and waste [4,5]. The efficiency of the nutrient transfer from the maternal to fetal systems affects the development of the fetus and thus influences prenatal survival in pigs.…”
Section: Introductionmentioning
confidence: 99%